Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4274/jcrpe.5456
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends, Regional Variability and Seasonality Regarding the Incidence of Type 1 Diabetes Mellitus in Romanian Children Aged 0-14 Years, Between 1996 and 2015

Abstract: Objective:The incidence of type 1 diabetes mellitus in children is highly variable in the world. The aim of our study was to: 1) analyze the evolution of the incidence of childhood type 1 diabetes in Romania between 1996 and 2015, and: 2) to search for differences amongst age groups, gender, geographic regions and month of diagnosis.Methods:Data on all new cases of type 1 diabetes, aged <15 years, obtained from two independent sources, were included in the study. The statistical methods included modeling of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The highest number of cases continues to be diagnosed in the older 10–14‐year age category in our population, and a number of other populations who have a similar incidence of T1DM to Ireland also show this trend, particularly Norway and Australia 2,10,24 . Some centres have shown the number of cases and incidence rates in the younger age categories are increasing suggesting a shift to an earlier age at diagnosis 6,12,13 . We have not found this.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The highest number of cases continues to be diagnosed in the older 10–14‐year age category in our population, and a number of other populations who have a similar incidence of T1DM to Ireland also show this trend, particularly Norway and Australia 2,10,24 . Some centres have shown the number of cases and incidence rates in the younger age categories are increasing suggesting a shift to an earlier age at diagnosis 6,12,13 . We have not found this.…”
Section: Discussionsupporting
confidence: 45%
“…In Ireland, the highest rates of T1DM have been predominately in the older 10–14 year age category to date 4,9 . This trend was seen in a number of other high incidence countries, such as Norway, 2 Australia, 10 Spain 1 and Canada, 11 while others report the highest increases in children aged under 5 years, such as Poland, 6 Hungary 12 and Romania 13 . Recent research has shown that countries with a lower overall incidence rates of T1DM have had a faster rise in T1DM incidence particularly in children aged under 5 years 12,13 .…”
Section: Introductionmentioning
confidence: 94%
“…In a three-year-long Dutch study including 676 children diagnosed with T1DM per year, the annual incidence rates per hundred thousand children were 6.6 and 6.4 in winter as opposed to 4.9 in spring and 5.4 in summer (p < 0.03) 19 . In 5422 children diagnosed with T1DM in Romania between 1996 and 2015, the maximum monthly incidence value was recorded in January (more than 450) as opposed to the minimum value recorded in June (around 300, p < 0.001) 20 . In 2174 Polish children diagnosed with T1DM between 2010 and 2014, the odds of diagnosis being made between June and August was 57% (95% confidence intervals: 51% to 67%, p < 0.0001) of the odds of diagnosing the disease between December and February 21 .…”
Section: Discussionmentioning
confidence: 90%
“…In addition to these mechanisms, viral infections [37] and/or vitamin de ciency [38] may also be involved. This seasonality is re ected in the high incidence rate of type 1 [37,39] and T2DM [40,41] during the coldest months. In agreement with previous ndings [36], the MAP at admission was signi cantly higher the present T2DM cohort in January than July over the 12-year study period (Table S2).…”
Section: Discussionmentioning
confidence: 99%